2020
DOI: 10.1186/s13031-020-0254-5
|View full text |Cite
|
Sign up to set email alerts
|

Male and LGBT survivors of sexual violence in conflict situations: a realist review of health interventions in low-and middle-income countries

Abstract: Conflict-related sexual violence (CRSV) against women and girls has been the subject of increasing research and scholarship. Less is known about the health of men, boys and lesbian, gay, bisexual, transgender (LGBT) and other gender non-binary persons who survive CRSV. This paper is the first systematic realist review on medical, mental health and psychosocial support (MHPSS) interventions that focusses on male and LGBT survivors of CRSV. The review explores the gender differences in context, mechanisms and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 111 publications
(227 reference statements)
1
22
0
9
Order By: Relevance
“…The specific barriers identified largely align with other studies that included documentation of barriers to service accessibility among male survivors in refugee settings [13,44]. Additional barriers emerged in other refugee settings, such as limited hours of operation that prohibited refugees who worked from accessing care [13], insecurity [44], the public nature of pursuing legal redress [13], and national laws stipulating the mandatory reporting of public officials [13].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The specific barriers identified largely align with other studies that included documentation of barriers to service accessibility among male survivors in refugee settings [13,44]. Additional barriers emerged in other refugee settings, such as limited hours of operation that prohibited refugees who worked from accessing care [13], insecurity [44], the public nature of pursuing legal redress [13], and national laws stipulating the mandatory reporting of public officials [13].…”
Section: Discussionmentioning
confidence: 54%
“…The specific barriers identified largely align with other studies that included documentation of barriers to service accessibility among male survivors in refugee settings [13,44]. Additional barriers emerged in other refugee settings, such as limited hours of operation that prohibited refugees who worked from accessing care [13], insecurity [44], the public nature of pursuing legal redress [13], and national laws stipulating the mandatory reporting of public officials [13]. More research on the specific service utilization barriers facing men, adolescents, and boy survivors, including those with physical, psychological, and intellectual disabilities, is warranted in other settings of forced displacement as well as a disaggregated approach to the specific barriers of persons with diverse SOGIESC, including gay men, trans women, trans men, lesbians, nonbinary persons, and intersex persons.…”
Section: Discussionmentioning
confidence: 62%
“…Anxiety and distress are a major ill in conflict affected contexts such as Afghanistan. Literature traditionally attributed mental distress to the violence itself (36)(37)(38)(39)(40) including sexual violence and intimate partner violence (41)(42)(43)(44). Increasingly, scholars have also shown that daily stressors play an important role in common and more severe mental disorders, particularly among vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%
“…PM and ADB will undertake a search of the literature in consultation with a University faculty librarian. Databases are likely to include Web of Science, Pubmed, EMBASE, MEDLINE, and PsycInfo, based on other reviews 31 conducted in the SSA context. We anticipate that the literature for this topic will be diverse and hence we will use extensive searching of grey sources, such as OpenGrey, Google Scholar and DODRIA – Africa’s data directory – for relevant documents.…”
Section: Methodsmentioning
confidence: 99%